Mutation analysis in Korean patients with T-cell acute lymphoblastic leukemia. (17th February 2020) - Park, Kyoung-Jin; Kim, In-Suk; Yang, Eu Jeen; Lim, Young Tak; Cho, Su-Hee
Abstract: Genomic studies have illuminated the alterations in pathways underlying T-cell acute lymphoblastic leukemia (T-ALL) pathogenesis, but detailed mutation data by next-generation sequencing have not been reported in Korean patients. We aimed to investigate mutation frequency, spectrum, and pattern in the Korean patients with T-ALL. We designed a multigene panel targeting 101 genes and validated it using 10 reference materials. The mutation analysis was done in a total of 10 patients with T-ALL. Clinical data and laboratory tests including immunophenotyping, cytogenetics, and molecular genetic tests were also investigated. All of the 10 patients harbored at least one mutation (range 1–6 per patient). A total of 34 clinically significant mutations including 15 novel mutations were identified in 23 genes. The median of variant allelic frequencies (VAFs) and blasts were counted upto 33% (range 5–91%) and 79% (range 38–90%), respectively. Recurrent mutations were involved in epigenetic regulators (60%), NOTCH1 signaling (40%), PI3K-AKT (40%), JAK-STAT (30%), and transcription factors (30%). We found that both NOTCH signaling and JAK-STAT signaling were positively associated with epigenetic regulators, while showed mutually exclusive patterns with PI3K-AKT pathway. This study showed that the frequency of mutations in epigenetic regulators in Korean patients was significantly higher than expected. Distribution of VAF as well as mutation spectrum is considerably heterogeneous in Korean patients with T-ALL. Although from a limited number of patients, this study provides the first detailed mutational portrait of T-ALL of Korean patients, and gives additional insight into molecular pathogenesis of the disease.